Algerian Acid Activated Clays as Efficient Catalysts for a Green Synthesis of Solketal by Chemoselective Acetalization of Glycerol with Acetone - Fouad Lebsir; Sondes Amri; Ali Rahmouni; Ezzedine Srasra; Néji Besbes; Kouider Alali (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The production of solketal and conversion of glycerol takes a major importance in the field of the sustainability of the biodiesel industry. The synthesis of (2,2-dimethyl-1,3-dioxolan-4-yl)methanol by the acetalization of glycerol with acetone successfully applied out using various Algerian acid activated clays (maghnia-H+) under autogenous pressure and without solvent. The acid catalyst clays are prepared by an easy technique by activation with the available and low-cost Maghnia clay. The purified Maghnia clay named ALC and the resulting series of acid-activated clays AL1, AL2, AL3, and AL4 are characterized by X-ray Fluorescence (XRF) investigation, N2-adorption/desorption Brunauer–Emmett–Teller  (BET) surface area, X-rays Diffraction (XRD), Fourier Transform Infra Red (FT-IR) spectroscopy, SEM microscopy and the cation exchange capacity (CEC) with copper bisethylenediamine complex method, in order to study the effect of activation at the acid and the catalytic behaviour in the acetalization reaction. The results show a high catalytic activity whose that the yield of solketal production interest reached 95 % at a temperature of 40 °C for a reaction time of 48 hours with full selectivity and glycerol conversion reaching up to 89 %. A mechanistic is proposed to explain the chemoselective of solketal production. These results indicate the potential of this Algerian acid activated clays catalysts for the acetalization of glycerol for an environmentally benign process.